Life domain preferences among women and men in Israel: The effects of socio‐economic variables. (19th January 2016) - SHARABI, Moshe
Abstract: Based on the findings of the 2006 "Meaning of Work" survey, this article examines the relative "life domain centrality" of work, family, leisure, community and religion across a representative sample of the Israeli labour force comprising 463 men and 446 women. While confirming that family centrality remained stronger among women than men, male and female respondents ranked work equally high, marking a departure from women's traditionally weaker preference for this life domain. Regression analysis identifies socio‐economic factors that partially explain the attitudinal differences between men and women. Overall, the results suggest a growing risk of work–family conflict among Israeli women.